Digital literacy of biology education students: Trends and differences based on semester level - Sri Wahyuni Sumadi; Nurhayati B; Faisal Faisal (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Twenty-first century skills are an important aspect in developing student competencies, one of which is digital literacy competency. Proficient digital literacy is needed in education, especially to support the technology-based learning process. This study aims to identify differences in the level of digital literacy of Biology Education students based on semester level. The research method used is a quantitative survey with a cluster random sampling technique. The sample of this study was biology education study program students in semesters 2, 4, and 6, with a total sample of 232 students. Data were analyzed using descriptive and inferential statistics, namely the ANOVA test, to determine whether there were significant differences in students' digital literacy skills between semesters. The results showed that the average digital literacy skills of students increased from semester 2 to semester 6, with consecutive scores of 41.20, 44.32, and 45.21. Despite the increase, the overall average is still very low. The results of the inferential statistical test, namely the ANOVA test, obtained a significance value of p = 0.000 (p < 0.05), which shows that there are differences in the digital literacy skills of students in different semesters. Therefore, a more optimal technology integration strategy in learning is needed, as well as lecturer competence in utilizing digital technology to strengthen student digital literacy.Abstrak. Keterampilan abad 21 merupakan aspek penting dalam pengembangan kompetensi mahasiswa, salah satunya yaitu kompetensi literasi digital. Literasi digital yang mumpuni sangat diperlukan dalam dunia pendidikan, terutama untuk mendukung proses pembelajaran berbasis teknologi. Penelitian ini bertujuan untuk mengidentifikasi perbedaan tingkat literasi digital mahasiswa Pendidikan Biologi berdasarkan tingkat semester. Metode penelitian yang digunakan adalah survei kuantitatif dengan teknik random sampling. Sampel penelitian ini adalah mahasiswa program studi pendidikan biologi semester 2, 4 dan 6, tahun akademik 2023/2024 dengan jumlah sampel sebanyak 232 mahasiswa. Data dianlisis menggunakan statistik deskriptif dan inferensial yaitu uji anova untuk menentukan terdapat perbedaan signifikan keterampilan literasi digital mahasiswa antar semester. Hasil penelitian menunjukkan bahwa rata-rata keterampilan literasi digital mahasiswa mengalami peningkatan dari semester 2 ke semester 6 dengan perolehan nilai berturut-turut sebesar 41,20, 44,32, dan 45,21. Meskipun terjadi peningkatan, rata-rata keseluruhan masih tergolong sangat rendah. Hasil uji statistik inferensial yaitu uji anova diperoleh nilai signifikansi p = 0,000 (p < 0,05) yang menunjukkan bahwa terdapat perbedaan keterampilan literasi digital mahasiswa pada semester yang berbeda. Oleh karena itu, diperlukan strategi pengintegrasian teknologi yang lebih optimal dalam pembelajaran, serta kompetensi dosen dalam pemanfaatan teknologi digital guna memperkuat literasi digital mahasiswa.